The Influence of The Level of Teacher Readiness in Implementing the “Merdeka Belajar” Curriculum - Mastur, Mastur (Universitas Majalengka, 2024)
The “merdeka belajar” curriculum was socialized more than one year ago. Every school is obliged to implement the curriculum to adapt to change, especially for driving schools that are pioneers, as well as pilot projects for new paradigm changes in the learning process. For this reason, school principals must prepare teachers as early as possible to be competent in following the existing rhythm of change. This study aims to analyze the influence of teacher readiness in implementing the independent learning curriculum in driving schools. This study used a quantitative approach, with 53 teachers selected as respondents using a saturated sampling technique. The research instrument used a questionnaire, and the data analysis technique used was multiple linear regression. The study's results found that intrinsic and extrinsic motivation significantly affected individual readiness to change, in this case, the teacher implementing the independent learning curriculum in driving schools. The results of this study are expected to provide input to school principals regarding motivating all teachers according to the characteristics and stages needed because every teacher has a different background.